Nitrite scavenging activities and reducing power capacities of ethanolic extracts of some fruits and vegetables - Can, Kubra; Sacan, Ozlem; Yanardag, Refiye (Bangladesh Journal of Botany, 2024)
The use of fruits and vegetables for therapeutic purposes has been continuing for centuries. Now-a-days, fruits and vegetables are increasingly used as alternative medicines. The antioxidant activities of some fruits and vegetables used in the present study were determined by nitrite scavenging and reduction power experiments. Antioxidant capacity increased with increasing concentration. The highest nitrite scavenging activity and inhibitory power were observed in garlic extract. The least nitrite scavenging activity and reducing power were found in white grape and kiwi extracts. It was concluded that garlic extract which had the highest nitrite scavenging capacity and reducing power may be an appropriate additive in drugs and other pharmaceuticals intended for medical purposes. Bangladesh J. Bot. 53(3): 619-625, 2024 (September)